Calcium Transient Assays for Compound Screening with Human iPSC-derived Cardiomyocytes: Evaluating New Tools - Neil J. Daily; Radleigh Santos; Joseph Vecchi; Pinar Kemanli; Tetsuro Wakatsuki (Journal of Evolving Stem Cell Research, 2017)
Calcium (Ca2+) plays a central role in regulating many biological processes in the cell from muscle contraction to neurotransmitter release. The need for reliable fluorescent calcium indicator dyes is of vast importance for studying many aspects of cell biology as well as screening compounds using phenotypic high throughput assays. We have assessed two of the latest generation of calcium indicator dyes, FLIPR Calcium 6 and Cal-520 AM for studying calcium transients (CaTs) in induced pluripotent stem cell (iPSC) -derived human cardiomyocytes. FLIPR Calcium 6 and Cal-520 dyes both displayed robust CaTs with a high signal-to-noise ratio (SNR) and were non-toxic to the cells. The analysis showed that CaT amplitudes were stable between measurements, but CaT duration was more variable and tended to increase between reads. Two methods were compared for drug-screening hit-selection; difference in average (unstandardized) and standardized difference. The unstandardized difference was better for assessing CaT amplitude, whereas standardized difference was equal to or better for assessing CaT duration. In summary, FLIPR Calcium 6 and Cal-520 are suitable dyes for drug-screening using iPSC-derived human cardiomyocytes.
Keywords: Calcium Transients